Tea Consumption and Health Outcomes: Umbrella Review of Meta‐Analyses of Observational Studies in Humans. Issue 16 (2nd July 2019) - Yi, Mengshi; Wu, Xiaoting; Zhuang, Wen; Xia, Lin; Chen, Yi; Zhao, Rui; Wan, Qianyi; Du, Liang; Zhou, Yong
Abstract : Scope: The aim of this article is to conduct an umbrella review to study the strength and validity of associations between tea consumption and diverse health outcomes. Methods and results: Meta‐analyses of observational studies examining associations between tea consumption and health outcomes in all human populations and settings are screened. The umbrella review identifies 96 meta‐analyses with 40 unique health outcomes. Tea consumption shows greater benefits than harm to health in this review. Dose–response analyses of tea consumption indicates reduced risks of total mortality, cardiac death, coronary artery disease, stroke, and type 2 diabetes mellitus with increment of two to three cups per day. Beneficial associations are also found for several cancers, skeletal, cognitive, and maternal outcomes. Harmful associations are found for esophageal and gastric cancer when the temperature of intake is more than 55–60 °C. Conclusion: Tea consumption, except for very hot tea, seems generally safe at usual levels of intake, with summary estimates indicating the largest reduction for diverse health outcomes at two to three cups per day. Generally, tea consumption seems more beneficial than harmful in this umbrella review. Randomized controlled trials are further needed to understand whether the observed associations are causal. Abstract : An umbrella review including 96 meta‐analyses with 40 unique outcomes is conducted to evaluate associations between tea consumption and health. An increment of two to three cups of tea per day is associated with reduced risk of total mortality, cardiac death, coronary artery disease, stroke, and type 2 diabetes mellitus. Except for very hot tea, which increases the risk of gastric and esophageal cancer, tea consumption seems generally safe.